High and Low Annealing Temperatures Increase Both Specificity and Yield in Touchdown and Stepdown PCR - Karl H. Hecker; Kenneth H. Roux (BioTechniques)
Touchdown (TD) PCR represents a versatile one-step procedure for optimizing PCRs even if the degree of primer-template complementarity is not fully known. The protocol relies on incremental annealing temperature decreases in progressive cycles designed to bracket the melting temperature (Tm) of the reaction. Here we investigate the characteristics of TD PCR that serve to minimize the need to optimize annealing temperature or buffer conditions and yet produce single strong target amplicons. We demonstrate that priming initiates above the optimum annealing temperature; this helps to ensure a competitive advantage for the target amplicon. On the other hand, as the cycling program progresses, annealing temperatures well below the Tm can serve to significantly increase yields in reactions that would otherwise be marginal due to suboptimal buffer composition and yet do not promote spurious amplification. Modified forms of TD PCR, termed stepdown PCR, consisting of fewer but steeper incremental declines in annealing temperature, are also shown to be effective and can simplify thermal cycler programming.